Improving intraoral implant scanning with a novel auxiliary device: An in‐vitro study. Issue 12 (27th September 2021) - Pan, Yu; Tsoi, James Kit Hon; Lam, Walter YH; Zhao, Ke; Pow, Edmond HN
Abstract: Objectives: To develop a novel auxiliary device for improving the accuracy of intraoral implant scanning in the complete‐edentulous arch. Materials and methods: A standard model of edentulous maxilla with six dummy implants was prepared. Scan bodies were attached to the model, which was scanned by a laboratory scanner. A simulated mucosa (Group 0), a resin base (Group 1), a resin base with a cuboidal reference block and 4 fiduciary spheres (Group 2) or artificial teeth (Group 3) in between the implants were mounted on the model, respectively. Each group were consecutively scanned using an intraoral scanner ( n  = 10). The scans were analysed for trueness and precision in inter‐implant distances and angles by inspection software. Effects of the auxiliary device and different quadrants on the accuracy of complete‐arch intraoral scanning were analysed by two‐way ANOVA. Results: Significant effects of the auxiliary device and quadrant were found on both linear and angular accuracies. The lowest linear accuracy was found in group 0. Group 1 and group 3 showed the best linear accuracy in quadrant 1 and quadrant 2, respectively. Group 2 showed the least angular precision among the three groups. Conclusions: The three designs of auxiliary devices significantly improved the accuracy of complete‐arch intraoral implant scanning. The base‐only design showed good scanning accuracy in a single quadrant, while the base with tooth‐shaped landmarks design showed better accuracy in cross‐arch. The fiduciary spheres might compromise the precision of scanning.